2011
DOI: 10.1074/jbc.m111.267922
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-36 (IL-36) Ligands Require Processing for Full Agonist (IL-36α, IL-36β, and IL-36γ) or Antagonist (IL-36Ra) Activity

Abstract: Background: IL-36 proteins are IL-1 family members with a key role in the skin. Results: Truncation of IL-36 ligands and IL-36Ra is required for full activity. IL-36Ra binds IL-1Rrp2 and prevents signaling. Conclusion:The mechanism of action of IL-36Ra is directly analogous to that of IL-1Ra. Significance: Protease(s) that activate IL-36 cytokines could be excellent drug targets for psoriasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
317
0
12

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 300 publications
(335 citation statements)
references
References 21 publications
6
317
0
12
Order By: Relevance
“…This indicated that sufficient IL-17A was still present in these supernatants that stimulated gene expression. As mentioned above, IL-36 cytokines require processing to gain biological activity [34][35][36] . IL-36 can be processed and activated by proteases derived from neutrophils 25,36 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…This indicated that sufficient IL-17A was still present in these supernatants that stimulated gene expression. As mentioned above, IL-36 cytokines require processing to gain biological activity [34][35][36] . IL-36 can be processed and activated by proteases derived from neutrophils 25,36 .…”
Section: Resultsmentioning
confidence: 99%
“…IL-36 cytokines that are induced in and secreted by NHEKs in response to IL-17A are inactive (Fig. 2), most likely because of lack of N-terminal processing 35 . In agreement with previous findings 25,36 , IL-36 can be activated by proteases that are released by activated neutrophils, including elastase (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations